BUSINESS RISK ATAUKAH HUMAN ERROR - Ulum, Miftachul (DIKTUM: Jurnal Syariah dan Hukum, 2018)
Abstract: In every decision made by the business, it is always confronted with an uncertainty that we know as risks. Stakeholders are those who influence or will be influenced by the decision. Statistically risk can be formulated as a deviation. The magnitude of risk can be measured by variance (Ï2) or standard deviation (Ï). Through prudential principles, the types and forms of risk can be avoided or minimized. The carelessness is a factor of human error which is a factor beyond human reason. Humans are only able to put the basic concept of prudence in making decisions but all the terms of haqiqi will be the right of the Almighty.  Abstraksi : Setiap pengambilan keputusan yang dilakukan oleh pelaku bisnis selalu dihadapkan  pada suatu ketidakpastian yang kita kenal dengan risiko. Stakeholder sebagai pemangku kepentingan merupakan pihak yang mempengaruhi atau yang akan dipengaruhi  keputusan tersebut. Secara statistik risiko dapat dirumuskan sebagai penyimpangan, besarnya risiko dapat diukur dengan variance (Ï2) atau standar deviasi. Melalui prinsip kehati-hatian jenis dan bentuk risiko dapat dihindari atau bahkan dapat diminimalkan. Kelalaian adalah   merupakan suatu  faktor yang diluar nalar manusia. Manusia hanya meletakkan konsep dasar kehati-hatian dalam mengambil keputusan namun ketentuan secara haqiqi menjadi hak Yang Maha Kuasa.